Substituting Coumarins for Quinolinones: altering the cycloreversion potential energy landscape - Paul, Nicholas; Jiang, Man; Pérez Lustres, José Luis; Li, Yang; Wollscheid, Nikolaus; Buckup, Tiago; Dreuw, Andreas; Hampp, Norbert; Motzkus, Marcus (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2018)
The light-activated cleavage of cyclobutane-based systems via [2 + 2] cycloreversions, such as thymine and coumarin dimers, is an important but still poorly understood ultrafast photochemical reaction. Systems displaying reversible cycloreversion have found various uses in cross-linked polymers, enhancing gas adsorption affinities in inorganics, and light-activated medical therapies. We report the identification of a heterogeneous mode of cycloreversion for a rarely examined coumarin analogue system. Quinolinone monomers and dimers were probed using ultraviolet pumped, transient absorption spectroscopy and demonstrated radically different photophysical properties than coumarins. Monomers displayed enhanced intersystem crossing at almost 1:1 versus the combined nonradiative and radiative singlet decay, while the dimers underwent cycloreversion to a one excited-one ground state monomer photoproduct pair. The change in both systems was directly linked to the lactame group in the quinolinone motif. This discovery highlights the dramatic effects that small chemical changes can have on photoreaction pathways and opens up a new means to produce and develop more efficient cycloaddition-cycloreversion systems.